An Economic Analysis of Kampung Chicken Production Using the Small Water Plant Azolla microphylla in Their Feed - Setiadi, Agus; Santoso, Siswanto Imam; Sumarsono; Mahfudz, L.D.; Susanto, A.B. (Pakistan Journal of Nutrition, 2016)
We investigated the physical appearance and feed cost of kampung chickens whose feed was supplemented with 20% Azolla in commercial feed. The experiment was carried out with 15-day-old kampung chicks assigned to two treatments. One hundred birds were used in the study, with 50 birds assigned to treatment 1 (T1) and 50 birds assigned to treatment 2 (T2). Birds in T1 received a control diet consisting solely of commercial feed, with the diet containing 210 g/kg of crude protein. Birds in T2 received a diet that included 20% Azolla microphylla (AM) mixed in the ‘commercial diet’; this diet contained 200.4 g/kg of crude protein. The experiments were conducted over a period of 8 weeks. No differences were found in feed consumption and the final weight of the birds, but birds who were fed the T2 diet had a better feed conversion ratio (FCR) (p